O efeito da musicoterapia organizacional na redução do nível de estresse de profissionais da saúde de um hospital público - Matoso, Leonardo Magela Lopes (Universidade Federal Rural do Semi-Árido, 2018)
A period of intense competitiveness, pressure and demand in the work environment is living in the contemporary world; with this, numerous occupational diseases, in particular stress, end up compromising workers' quality of life and organizational dynamics. Thus, the objective of this study was to analyze the influence of receptive organizational music therapy on the stress levels of nursing professionals in a public hospital. In order to reach the proposed objective, an applied research, of an explanatory nature, with a quasi-experimental procedure was carried out, complemented with systematic observation and episodic interviews, in a mixed approach. The research universe was 200 nursing professionals at the technical and higher level. They answered a sociodemographic questionnaire for their characterization and had their stress levels measured by the Inventory of Stress Symptoms for Adults of Lipp. The initial results indicated that of the 200 professionals, 32% were classified without any level of stress. In contrast, 68% of the participants were at some level of stress. Of the professionals who were under stress, 45% were in the second phase, known as resistance; 14.5% were in the third stage, termed quasi-exhaustion; 7% were classified in the first stage of stress, known as alert; and 1.5% in the last phase, classified as exhaustion. Of the 200 participants, 74 were selected to participate in organizational receptive music therapy. After 30 days of receptive music therapy, the 74 professionals who participated in this experiment had their stress levels reassessed and compared to stress levels prior to musical intervention using the Wilcoxon test. The results of the test showed that stress levels in the phases of resistance, quasi-exhaustion and exhaustion were minimized after musical application. In turn, the alert phase increased considerably after the musical intervention, and this is positive, considering that it is considered as the manifestation phase of eustresse. This was due to the fact that the professionals who were in the phases of exhaustion and quasi-exhaustion had their stress indexes reduced respectively to the phase of quasi-exhaustion and resistance. On the other hand, the participants in the resistance phase had their stress levels reduced to alert phase and those who were in the alert phase after the application of music therapy did not have the necessary symptoms to be framed with stress. Given this, and based on the statistical test and guided by the episodic interview, it was concluded that receptive organizational music therapy had significant effects on the reduction of stress and on the improvement of the quality of life in the professionals' work. Finally, it is believed that the use of music in the organizational environment is an innovative strategy of humanized care for health professionals
Keywords: Musicoterapia organizacional; Estresse; Quase-experimental; Hospital; Organizational music therapy; Stress; Semi-experiment; Hospital; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES